Preparing Methane – Air Mixture Using Ejector - Jabbar, Tahseen Ali; Hasan, Masad Mezher; Faisal, Safaa Hameed (Basrah Journal for Engineering Sciences, 2021)
In this research, a two – dimensional numerical investigation is conducted to show the ability of the jet-ejector to prepare the air – methane mixture at different equivalence ratio. The basic dimensions (diameters ratio, throat length, angle α , and angle θ ) of the jet-ejector are taken into account on calculating the equivalence ratio. The results showed that the ratio of the diameters has a higher effect than other parameters on preparing a mixture for equivalent ratios including both rich and lean mixture. The rest of the factors did not have a significant effect on the value of the equivalence ratio, and only had a role in preparing an equivalence ratio for rich mixture type.